Development and validation of a Self‐assessment Instrument for Perioperative Patient Safety (SIPPS). Issue 6 (13th July 2018) - Heideveld‐Chevalking, A. J.; Calsbeek, H.; Griffioen, I.; Damen, J.; Meijerink, W. J. H. J.; Wolff, A. P.
Abstract : Background: Patient safety is a fundamental value of healthcare to avoid patient harm. Non‐compliance with patient safety standards may result in patient harm and is therefore a global concern. A Self‐assessment Instrument for Perioperative Patient Safety (SIPPS) monitoring and benchmarking compliance to safety standards was validated in a multicentre pilot study. Methods: A preliminary questionnaire, based on the Dutch perioperative patient safety guidelines and covering international patient safety goals, was evaluated in a first digital RAND Delphi round. The results were used to optimize the questionnaire and design the SIPPS. For measurement and benchmarking purposes, SIPPS was categorized into seven main patient safety domains concerning all care episode phases of the perioperative trajectory. After consensus was reached in a face‐to‐face Delphi round, SIPPS was pilot‐tested in five hospitals for five characteristics: measurability, applicability, improvement potential, discriminatory capacity and feasibility. Results: The results of the first Delphi round showed moderate feasibility for the preliminary questionnaire (81·6 per cent). The pilot test showed good measurability for SIPPS: 99·8 per cent of requested information was assessable. Some 99·9 per cent of SIPPS questions were applicable to the selected respondents. With SIPPS, room for improvement in perioperative patient safety compliance was demonstrated for all hospitals, concerning all safety domains and all care episode phases of the perioperative trajectory (compliance 76·1 per cent). SIPPS showed mixed results for discriminatory capacity. SIPPS showed good feasibility for all items (range 91·9–95·7 per cent). Conclusion: A self‐assessment instrument for measuring perioperative patient safety (SIPPS) compliance meeting international standards was validated. With SIPPS, improvement areas for perioperative patient safety and best practices across hospitals could be identified. Abstract : A Self‐assessment Instrument for Perioperative Patient Safety (SIPPS) monitoring and benchmarking compliance to safety standards was developed and validated in a multicentre pilot study. Merits evaluation in other health care systems.